Spatial Thinking in Conic Sections: A Study of Undergraduate Mathematics Students by Sex and Spatial Category - Dintarini, Mayang; Budiarto, Mega Teguh; Fuad, Yusuf (Mathematics Education Journal, 2025)
Spatial thinking plays an important role in solving conic section problems. When students encounter problems involving shapes like parabolas, ellipses, and hyperbolas, they need not only grasp the algebraic representations but also visualize how a plane intersects a cone in three-dimensional space. Unlike previous studies that focused on psychometric tasks disconnected from classroom content, this study integrates spatial thinking directly into mathematical problem-solving, specifically in conic sections. The study examines undergraduate students' spatial thinking skills on conic sections, based on spatial thinking categories and sex differences. Twenty-five undergraduate students (4 males and 21 females) from the Mathematics Education Department at Universitas Muhammadiyah Malang, enrolled in an analytical geometry course and participated in a spatial thinking test. Additionally, four students (2 males and 2 females), representing both high and low spatial thinking abilities, were interviewed to provide deeper insights into students' spatial thinking. The results show that students with high spatial thinking abilities demonstrated strong mental visualization skills but had minor difficulties and errors in representing detailed components. Moreover, students with lower spatial thinking abilities have difficulties in visualizing complex objects and often misinterpret spatial representations. Furthermore, male students provided limited written explanations of spatial object characteristics, whereas female students faced difficulties in accurately drawing 3D spatial objects but compensated with effective 2D representations and verbal explanations. In conclusion, the findings show that the difficulties of spatial thinking are influenced by spatial thinking categories and gender differences, offering rich information to design more effective mathematics learning.